Computational Systems Bioinformatics: Methods and Biomedical Applications - Xiaobo Zhou (World Scientific, 2008)
Computational systems biology (CSB) is a field of research concerned with understanding the structure and processes of biological systems at the molecular, cellular, tissue, and organ levels through computational modeling as well as novel information theoretic data and image analysis methods. This book introduces the basic principles of CSB